“Plan de MP para flota mediana del centro de distribución de Pucallpa de la corporación ABinbev - Julca Ulloa, Jesus Alberto (2023)
The present work proposes actions that integrate a PMP, which will increase the availability of the medium fleet in the ABINBEV Corporation. which is located in the town of Pucallpa, Ucayali. It has 18 units with which it carries out its work. Currently the company has preventive maintenance plans focused on the recommendations provided by the manufacturer; however, there is a high annual cost of corrective maintenance that could be optimized with an adequate preventive maintenance plan that not only includes the manufacturer's recommendations.